Distribution and Economic Progress: A Revised Version - Hicks, J. R. (Review of Economic Studies, 1936)
Journal Article Distribution and Economic Progress: A Revised Version Get access J. R. Hicks J. R. Hicks Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 1, October 1936, Pages 1–12, https://doi.org/10.2307/2967656 Published: 01 October 1936